2019
DOI: 10.1126/science.aav1910
|View full text |Cite
|
Sign up to set email alerts
|

Tuning superconductivity in twisted bilayer graphene

Abstract: Materials with flat electronic bands often exhibit exotic quantum phenomena owing to strong correlations. Remarkably, an isolated low-energy flat band can be induced in bilayer graphene by simply rotating the layers to 1.1 • , resulting in the appearance of gate-tunable superconducting and correlated insulating phases. Here, we demonstrate that in addition to the twist angle, the interlayer coupling can also be modified to precisely tune these phases. We establish the capability to induce superconductivity at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

114
1,811
7
9

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,032 publications
(1,941 citation statements)
references
References 84 publications
114
1,811
7
9
Order By: Relevance
“…Experimentally, the “magic angle” graphene with a small amount of electrons can present a superconducting state at the temperature of 1.7 K (Figure e) . That means one can regulate TBG between insulators and superconductors . In addition, more different angles of TBG can be created and more physical phenomena could be explored in a single device .…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, the “magic angle” graphene with a small amount of electrons can present a superconducting state at the temperature of 1.7 K (Figure e) . That means one can regulate TBG between insulators and superconductors . In addition, more different angles of TBG can be created and more physical phenomena could be explored in a single device .…”
Section: Introductionmentioning
confidence: 99%
“…The insulating states, believed to be due to electronic correlations [1], were originally observed when the charge per moiré cell is ±2 with respect to the charge neutrality point (CNP). More recently, insulating states when the twisted bilayer graphene (TBG) is doped with 1 or 3 carriers have also been observed [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentalists are able to isolate layers of different materials only one‐atom, or few‐atoms, thick, and to combine such layers with increasing control of the stacking configuration. A striking example of this tunability is the recent experimental realization of vdW systems formed by two graphene layers in which the stacking angle, twist angle, can be adjusted to within a fraction of a degree . These experiments have shown that, by tuning the relative twist angle between graphene layers, the system can become superconducting or insulating.…”
Section: Introductionmentioning
confidence: 99%
“…A striking example of this tunability is the recent experimental realization of vdW systems formed by two graphene layers in which the stacking angle, twist angle, can be adjusted to within a fraction of a degree . These experiments have shown that, by tuning the relative twist angle between graphene layers, the system can become superconducting or insulating. These remarkable results are just one example of the ways in which vdW heterostructures can be used to realize electronic systems with exotic and desirable properties.…”
Section: Introductionmentioning
confidence: 99%